Computational analysis of customized cruciate retaining total knee arthroplasty restoration of native knee joint biomechanics. Issue 5 (12th December 2018) - Koh, Yong‐Gon; Lee, Jin‐Ah; Chung, Pill Ku; Kang, Kyoung‐Tak
Abstract: The purpose of this study was to verify if customized prosthesis better preserves the native knee joint kinematics and provides lower contact stress on the polyethylene (PE) insert owing to the wider bone preservation than that of standard off‐the‐shelf prosthesis in posterior cruciate‐retaining type total knee arthroplasty (TKA). Validated finite element (FE) models for were developed to evaluate the knee joint kinematics and contact stress on the PE insert after TKA with customized and standard off‐the‐shelf (OTS) prostheses as well as in normal healthy knee through FE analysis under dynamic loading conditions. The contact stresses on the customized prosthesis decreased by 18% and 8% under gait cycle loading conditions, and 24% and 9% under deep‐knee‐bend loading conditions, in the medial and lateral sides of the PE insert, respectively, compared with the standard OTS prosthesis. The anterior‐posterior translation and internal‐external (IE) rotation in customized TKA were more similar to native knee joint behaviors compared with standard OTS TKA under gait loading conditions. The difference from normal knee kinematics was lower for femoral rollback and IE rotation in customized TKA than in standard OTS TKA in the deep‐knee‐bend condition. In general, customized prostheses achieve kinematics that are close to those of the native healthy knee joint and have better contact stresses than standard OTS prostheses in gait and deep‐knee‐bend loading conditions.